2022
DOI: 10.1038/s41598-022-17363-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tooth loss and hypertension: a systematic review and meta-analysis

Abstract: As tooth loss is the high end of periodontal problems and edentulous individuals are at higher risk of nutritional problems like obesity, understanding the association between tooth loss and hypertension is important for improving cardiovascular health. We searched for publications from the last two decades using three electronic databases (PubMed, Web of Science and Scopus) and conducted a systematic review and meta-analysis on the association between tooth loss and hypertension according to PRISMA-P guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Our analysis did not differentiate between cause and effect, and therefore we can assume that, in this case, a smaller number of teeth influences the greater expression of CVDs. The literature mentions associations between tooth loss and increased risk of hypertension ( 20 ), coronary heart disease ( 38 ), peripheral arterial disease ( 39 ), and myocardial infarction ( 40 ). Although our results suggest that CVDs negatively influence the number of teeth, further studies are needed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis did not differentiate between cause and effect, and therefore we can assume that, in this case, a smaller number of teeth influences the greater expression of CVDs. The literature mentions associations between tooth loss and increased risk of hypertension ( 20 ), coronary heart disease ( 38 ), peripheral arterial disease ( 39 ), and myocardial infarction ( 40 ). Although our results suggest that CVDs negatively influence the number of teeth, further studies are needed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the existing literature has highlighted evidence of a relationship between systemic chronic diseases and tooth loss. Studies have shown that systemic health conditions, such as diabetes mellitus (DM) ( 13 , 14 ), rheumatoid arthritis ( 15 ), osteoporosis ( 16 ), neurodegenerative diseases ( 17 , 18 ), liver diseases ( 19 ), hypertension ( 20 ), and stroke ( 21 ) can impact oral health, potentially leading to issues such as periodontal disease and tooth loss and vice versa. The number of retained teeth is also a predictor of mortality ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, hypertension is considered a risk factor for tooth loss due to periodontal disease [ 19 ]. It has been speculated that increased blood pressure is likely to cause both the spread of inflammation and secondary damage to the vascular endothelium [ 20 ]. These factors might affect the development of a DOI, but the exact mechanism of DOI development remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, in actual orthodontic plan formulation, factors like the patient's specific situation, the dentist's experience and professional opinion, and the limitations of treatment equipment should also be considered. Therefore, it is advised to have detailed discussions and consultations with a professional orthodontist before treatment to ensure the development of the most suitable orthodontic plan for the patient [7][8][9][10].…”
Section: Developing a Reasonable Orthodontic Plan Including Direction...mentioning
confidence: 99%